Art Athina 2 '94 : Contemporary Art Fair. (Athens : Hellenic Art Galleries Association Athens, 1994)
Abravanel, Eliana ; Adamakis, Yannis ; Adamakos, Alexis ; Barclay, Per ; Baselitz, Georg ; Bonatsos, Stavros ; Cacoyannis, Panayotis ; Calzolari, Pier Paolo ; Cambadakis, Kyriakos ; Dambassine, Lydia ; De Maria, Nicola ; Dionyssopoulos, Vassilis ; Fanakides, Apostolos ; Galanou, Sofia ; etc.
Art Athina 2 '94 : Contemporary Art Fair, Athens Exhibition Centre, Athens, 10-15 May 1994
boek